(untitled) (Eurasian Research Bulletin, 2023)
1,3,4-thiadiazole-2,5-dithiol organic reagent is used as analytical reagent for lead(II) ion. The possibility of their immobilization in fiber carriers and their use as a specific analytical reagent for the determination of metal ions, particularly lead (II) ion, has been developed. A simple, express method for the determination of lead (II) ion using 1,3,4- thiadiazole-2,5-dithiol organic reagent is shown. The reagent reacts with lead (II) ion in a ratio of 1:6.